« Jules Crevaux, l’explorateur aux pieds nus ». Un mythe géographique amazonien - Emmanuel Lézy (EchoGéo)
The rejection by Lévi Strauss of the explorer organise his own exploration of Amazonia as much as his quest for the Indian. The scientist, between those two characters, holds a medium position between blindness and foresight. The « voyage », stuck by the same despise, is presented as a caricature of indigenous nomadism. The exploration of the countries of totemism and animism is described as a mental, intelectual activity based on the identification of the fundamental structures of the myths organising the knowledge of the world which has nothing to do with the necessary movement of the feet. Nevertheless, the carefull observation of the feet of an amazonian explorer, Jules Crevaux (1847-1882), reveals structures which are common to the covered territory and to a modern mythology. This structures give an unexpected confirmation of the efficiency of the anthropologist’s analyses.